Cloning, expression, and purification of Acrv tip protein from Aeromonas hydrophila using Escherichia coli host cells - Sang, Nguyen Van; Uyen, Nguyen Thi (Academia Journal of Biology, 2021)
Aeromonas spp. use T3SS to secrete and transport effector proteins to the host cells. These proteins play a major role in bacteria virulence by interfering with the signaling cascades and by disrupting the cytoskeleton structure of the host cell. Despite tremendous efforts, structural and functional information regarding AcrV tip protein of T3SS remains elusive. In this study, we cloned the gene encoding the AcrV protein from Aeromonas hydrophila AH-1 and inserted it into the pET-M expression vector. The pET-M vector containing AcrV gene was transformed and expressed in E.coli BL21 (DE3) cells. The recombinant AcrV protein was purified by affinity chromatography using Ni-NTA column. The obtained AcrV with high purity can be used for structural and functional studies.